Peningkatan Hasil Belajar Tema 8 Menggunakan Model Everyone is Teacher Here di Kelas IV SD Negeri 02 Aur Kuning Kota bukittinggi - Yessy Fitri; Mai Sri Lena (e-Jurnal Inovasi Pembelajaran Sekolah Dasar, 2021)
The purpose of the research was to describe the improvement of students’ learning outputs of “Tema 8” by implementing “Everyone is Teacher Here” model at Four Grade Students of SD Negeri 02 Aur Kuning Kota Bukittinggi. This research was a classrom actiion reasearch which used qualitatiive and quantitatiive approaches. It was implemented in two cycles, they were cycle one and cycle two. Cycle I was administered  during two meetings and cycle II was constructed in 1 meeting. The subjekt of the research was the teacher at the four grade as observer, researcher as practitioner, and the four grade students of elementarry school 02 Aur Kuning Kota Bukittinggi (31 students). The results of the research showed the improvement of students’ learning output, they were : a) observation results of the lesson plan (RPP) in cycle I 85,22%, it increased in cycle II became 93,18%. b) The result of teacher’s activities in cycle I : 85%, it increased into 92,5%. c) the result of students’ activities in cycle I : 86,25%, it increased in cylce II : 92,5%. d) Students’ learning assessment at cycle I is avaraged 79,06% with 64,51% furthermore it was increased in cycle II became 87,10%. Based on these results, it can be concluded that “Everyone is Teacher Here” model can improve students’ learning output of “Tema 8”.